Comparison of the Marginal Fitness of the Ceramic Crowns Fabricated with Different CAD/CAM Systems (An In Vitro Study) - Abdulkareem, Akram M.; Ibraheem, Adel F. (Journal of Baghdad College of Dentistry, 2016)
Background: The marginal fit is the most characteristic that closely related to the longevity or success of a restoration, which is absolutely affected by the fabrication technique. The objective of present in vitro study was to evaluate the effect of four different CAD/CAM systems on the marginal fit of lithiÂµm disilicate all ceramic crowns.Materials and Methods: Adentoform tooth of a right mandibular first molar was prepared to receive all ceramic crown restoration with deep chamfer finishing line (1mm) and axial reduction convergence angle of 6 degree, dentoform model duplicated to have Nickel-ChromiÂµm master die. Thirty two stone dies produce from master die and distributed randomly in to four groups (8 dies for each group) according to the type of CAD/CAM system that used: Group A: fabricated with CERAMILL motion2 (Amann Girrbach); Group B:fabricated with CEREC in lab MCXL (Sirona);Group C: fabricated with CORiTEC 250i (imes-icore); Group D: fabricated with ZIRKONZAHN M5 (Zirkonzahn). Marginal discrepancy was measured at four points at each tooth surface. Sixteen points per tooth were measured using digital stereomicroscope at (140X) magnification.Results: ANOVA and LSD post Hoc tests were used to identify and localize the source of difference among the groups. It was found that there is a highly significant difference in the marginal gap mean values between group C and group D, and highly significant differences between group A and group D.Conclusions: From the above result we can conclude that better marginal fit values were may be exhibited by CORiTEC 250i CAD/CAM system.